(untitled) (Libellarium: journal for research in the field of information and related sciences, 2023)
Purpose. The purpose of the article was to identify the structural elements that should be present in the biographies that are included in online biographical lexicons. We are also interested in the criteria or structural elements that could help to decide which personalities to include in the online biographical lexicon. Methodology. Content analysis was used to analyze the structure of biographies that are entered in the online biographical lexicon. The same method was used to determine the criteria for selecting the personalities for entry into the online biographical lexicon. Results. The criteria for the selection of personalities into the OSP online biographical lexicon and the structure of biographies are defined. It is concluded that it is desirable for the order of the structural elements to be permanent. For the development of biographical lexicons, cooperation between all institutions that can contribute to the quality of biographical lexicons is essential. Research limitation. The research limitations presented the fact that the data about each personality to be included in the online biographical lexicon is unique. Thus, it is very difficult to determine unique structural elements for all personalities because they are engaged in very different activities. In addition, to our knowledge, there is no research work related to the structure of biographies in biographical lexicons. Originality/practical implications: The results of the research can contribute to the quality of the entries for the online biographical lexicon OSP and other online biographical lexicons. Better structure of biographies and professional criteria for selecting personalities should also have an impact on user satisfaction with the biographical lexicon. This article is also an invitation for further research work in this area.